2020
DOI: 10.1016/j.ebiom.2020.102853
|View full text |Cite
|
Sign up to set email alerts
|

A targeted reactivation of latent HIV-1 using an activator vector in patient samples from acute infection

Abstract: Background During combined anti-retroviral treatment, a latent HIV reservoir persists within resting memory CD4 T cells that initiates viral recrudescence upon treatment interruption. Strategies for HIV-1 cure have largely focused on latency reversing agents (LRAs) capable of reactivating and eliminating this viral reservoir. Previously investigated LRAs have largely failed to achieve a robust latency reversal sufficient for reduction of latent HIV pool or the potential of virus-free remission in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…These APCs will ultimately present HIV-1 antigens on MHC class II to CD4 + T cells with TCR specific to these HIV-1 antigens, leading to activated CD4 + T cells, which are now susceptible to HIV-1 infection and replication [ 168 ]. We hypothesize that this cycle of HIV-1 antigen presentation and activation of HIV-specific T cells leads to a skewing of the antigen-specificity of latently infected cells towards HIV-1 antigens [ 169 ]. This hypothesis is supported by the observation that most variants in the reservoir arose from strains circulating immediately prior to ART initiation [ 10 , 81 , 82 ]: once ART is initiated and HIV-1 antigens are cleared HIV-specific T cells will revert to a resting state en masse .…”
Section: The Current State Of Art In Lmicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These APCs will ultimately present HIV-1 antigens on MHC class II to CD4 + T cells with TCR specific to these HIV-1 antigens, leading to activated CD4 + T cells, which are now susceptible to HIV-1 infection and replication [ 168 ]. We hypothesize that this cycle of HIV-1 antigen presentation and activation of HIV-specific T cells leads to a skewing of the antigen-specificity of latently infected cells towards HIV-1 antigens [ 169 ]. This hypothesis is supported by the observation that most variants in the reservoir arose from strains circulating immediately prior to ART initiation [ 10 , 81 , 82 ]: once ART is initiated and HIV-1 antigens are cleared HIV-specific T cells will revert to a resting state en masse .…”
Section: The Current State Of Art In Lmicsmentioning
confidence: 99%
“…This hypothesis is supported by the observation that most variants in the reservoir arose from strains circulating immediately prior to ART initiation [ 10 , 81 , 82 ]: once ART is initiated and HIV-1 antigens are cleared HIV-specific T cells will revert to a resting state en masse . The use of HIV-1 antigens as an immunogen could specifically reactivate and eliminate this substantial portion of the reservoir [ 169 ], We have recently developed heterogenous virus-like particle (VLP) derived from the quasi-species of five HIV-1 infected patients [ 169 , 170 ]. This VLP formulation contains all the HIV-1 proteins and is morphologically identical to wild type HIV-1 but lacks genomic RNA and has additional mutations to ensure it is not replication-competent and can be tested as a cure therapeutic [ 170 ].…”
Section: The Current State Of Art In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this was demonstrated by Simonetti et al (2016) who observed extensive clonal expansion in the presence of cancer metastases, suggesting that an infected cells harboring a replication-competent sequence variant proliferated in response to a cancer antigen. Similarly, others have hypothesized that a chronic state of immune activation, caused by the continuous activation of infected cells leading to the release HIV-1 antigens, drives the clonal expansion of HIV-1 targeting reservoir cells ( Mann et al. 2020 ).…”
Section: Analyzing Reservoir Sequencesmentioning
confidence: 99%
“…Mann et al study describes a “shock and kill” strategy that employs the activator vector termed ACT-VEC, a polyvalent virus like particle (VLP) formulation combining HIV quasi-species from five chronic HIV-infected volunteer's plasma samples taken immediately prior to cART initiation [ 7 ]. ACT-VEC are viral-like particles similar to human papillomavirus (HPV) VLPs used in multivalent HPV vaccines, with the advantages of increased antigenic breadth and generation a broader immune response, along with a suitable margin of safety and efficiency.…”
mentioning
confidence: 99%